Mucin-1: a promising pan-cancer therapeutic target - Udhayvir Singh Grewal; Razelle Kurzrock (npj Precision Oncology)
Abstract Mucin1 or MUC1 (also known as CD227, EMA, MCD, MAM6, PEM, PUM, KL-6, CA 27.29/CA 15-3) is a highly glycosylated transmembrane mucin family member protein that is overexpressed in various solid or hematological cancers. Abnormal MUC1 expression/glycosylation in cancer leads to the activation of multiple pathways, resulting in tumor migration, invasion and accelerated growth. CA 27.29/CA 15-3 are blood tumor markers used in breast cancer patients. Novel therapeutic agents targeting MUC1, including cancer vaccines, cellular therapies, radiopharmaceuticals, monoclonal antibodies and antibody-drug conjugates, are being explored in clinical studies. The current review summarizes the molecular mechanisms of MUC1 in cancer and highlights existing data for MUC1-targeting agents in the therapeutic pipeline.